Pkm Appropriate Technology Training for Making Granule Organic Fertilizers in Gogodeso and Munggalan Villages - Irawan, Dani; Bisono, Rahayu Mekar (Universitas Nusantara PGRI Kediri, 2019)
One of the activities of the